Design of a Full-Range Capacitive Sensor Extensometer Using a High-Precision Ultrasonic Motor - Chen Dou; Wenbo Wang; Hong Li; Yunkai Dong; Weiwei Zhan; Liheng Wu; Jiaxin Chen (Sensors)
Extensometers are critical instruments for accurately measuring small displacements in terrain deformation monitoring. Conventional extensometers often employ eddy current displacement sensors or differential transformer sensors, which are constrained by structural limitations that hinder their ability to meet high-precision requirements. The capacitive micro-displacement sensor has a high precision of up to 0.1 µm, but it is typically limited by its measurement range, making it unsuitable for directly capturing rapidly changing geological phenomena such as earthquakes and landslides. This range limitation can result in exceedance and measurement errors, severely compromising the reliability and timeliness of the data. To address these challenges, this study introduces a novel design for a full-range capacitive sensor extensometer powered by a high-precision ultrasonic motor. The system integrates an ultrasonic motor with high-sensitivity capacitive sensors, enhanced by a grating scale and PID control algorithms. By enabling real-time signal processing and adaptive correction, the proposed design ensures a wide measurement range while significantly improving the measurement stability and accuracy. Laboratory experiments and field validations confirm the extensometer’s performance, achieving a resolution of 2.0 × 10−11 strain, a linearity of 0.024%, and a calibration repeatability of 0.06%. These results meet the stringent requirements of terrain deformation observation and establish the extensometer as a robust solution for micro-displacement measurements. This innovative design enhances the reliability of terrain deformation monitoring and contributes to the advancement of rock mechanics observation technologies.